Gateway cities for transnational higher education? Doha, Dubai and Ras al-Khaimah as regional amplifiers in networks of the `global knowledge-based economy' - Tim Rottleb (Global Networks, 2022)
This paper investigates how the developmental ambitions of governments to attract university offshore campuses to Doha, Dubai and Ras al-Khaimah and these universities' internationalization strategies affect the three cities' positionalities. It links interdisciplinary literature on globally uneven geographies of higher education to geographical debates on the intermediating role of cities in regional and global economies. The paper conceptualizes the three cities as a triadic ensemble of gateways for transnational higher education (TNE), thereby contributing to further theorization of gateway cities. The paper shows that the three cities fulfil two crucial gateway functions. First, they connect internationalizing universities with particular student segments from their regional hinterlands seeking access to TNE. Second, they thereby amplify and disperse hegemonic regimes of the globalising knowledge-based economy in their regional hinterlands. While all three cities share similar functions and rationales, they also have distinct positionalities rooted in different strategies of the respective governments.
Keywords: 320; Arab Gulf; gateway cities; globalization; knowledge-based economy; transnational higher education